2012
DOI: 10.1108/01443571211195736
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the impact of strategic sourcing and flexibility on firm's supply chain agility

Abstract: This is the submitted version of the paper.This version of the publication may differ from the final published version. Purpose -The objective of this study is to investigate two potentially key drivers of a firm's supply chain agility, namely strategic sourcing and firm's strategic flexibility. Despite some theoretical and conceptual works suggesting that some elements of these two constructs may relate to agility, this has not yet been assessed together empirically. This study aims to address this gap in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(176 citation statements)
references
References 95 publications
(183 reference statements)
7
164
1
4
Order By: Relevance
“…Therefore, the alignment with corporate goals and cross-functioning is still an important factor that the sourcing function needs to adapt to (Moses and Åhlström, 2008). Furthermore, the supplier management and partnerships, continuous improvement, employees, supply flexibility and total cost of ownership (Narasimhan and Das, 1999;Kocabasoglu and Suresh, 2006;Su et al, 2009;Chiang et al, 2012) were identified as significant factors and are mainly in line with previous research, although these were only mentioned by around half of the companies.…”
Section: "Continuous Improvement I Think That Goes Through Everythinsupporting
confidence: 71%
See 3 more Smart Citations
“…Therefore, the alignment with corporate goals and cross-functioning is still an important factor that the sourcing function needs to adapt to (Moses and Åhlström, 2008). Furthermore, the supplier management and partnerships, continuous improvement, employees, supply flexibility and total cost of ownership (Narasimhan and Das, 1999;Kocabasoglu and Suresh, 2006;Su et al, 2009;Chiang et al, 2012) were identified as significant factors and are mainly in line with previous research, although these were only mentioned by around half of the companies.…”
Section: "Continuous Improvement I Think That Goes Through Everythinsupporting
confidence: 71%
“…Furthermore, Chiang et al (2012) show that strategic sourcing and strategic flexibility are significant influences on the agility of supply chains. The determination of strategic sourcing by strategic purchasing, supplier development, internal integration and information sharing has a greater influence on a firm's supply chain agility than flexibility.…”
Section: Strategic Sourcing Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many scholars see the need of strategic sourcing and its positive impact on organisations' performance and competitive advantage (Kocabasoglu and Suresh, 2006;Chiang et al, 2012), this research reveals that strategic sourcing is still an emerging function within the both electronics manufacturing and construction organisations in Germany and the UK. This study also finds that the adoption of strategic sourcing in the UK organisations is more than in Germany, and the practices of strategic sourcing in the construction organisations is less than that in the electronics manufacturing organisations.…”
Section: Discussionmentioning
confidence: 99%